Simulation of the purification process of waste cooking oil as a feedstock for biodiesel production - Miguel A. Guerrero-Muñoz; Karla E. Mares-Molina; José J. Tovar-Negrete; Salvador Hernández; Fabricio O. Barroso-Muñoz (Chemical Engineering Transactions, 2024)
In the present work, the simulation of the purification process of waste cooking oil (WCO) as feedstock for biodiesel production was simulated using Aspen Plus TM V11.0. The process was simulated considering the compositions of the waste cooking oils in the central region of Mexico, specifically in the center of the state of Guanajuato. The equipment necessary to separate the ash and organic food waste were considered in the process simulation. It is necessary to consider that waste cooking oil contains a large amount of free fatty acids, which could cause saponification in the case of using the basic route to produce biodiesel. Kinetic model and thermodynamics model were taken from literature. As initial part of the process simulation a decanter was included. Therefore, the process was simulated to reduce the amount of free fatty acids and remotion or ashes and water from waste cooking oil. Finally, the purified oil contains, less than 1% by weight of free fatty acids, which makes it ideal for producing biodiesel by basic transesterification or any other route for biodiesel production. These results were consistent with the experimental results reported in the literature.